Differential regulation of MMP activity by TGFβ1 in fast- and slow- twitch muscle repair: insights from EDL and soleus muscle-derived myoblasts - Kasprzycka, Paulina; Ciemerych, Maria Anna; Zimowska, Malgorzata (Frontiers in Cell and Developmental Biology, 2025)
IntroductionSkeletal muscles are characterized by a significant ability to regenerate in response to injury. However, muscle repair is often inefficient and hindered by the development of fibrosis. The course of muscle repair is related to the type of skeletal muscle, i.e., fast- versus slow-twitch, and is controlled by various factors. Among them are TGFβ1 and two MMPs, i.e., MMP-2 and MMP-9 gelatinases that play a key role in the remodeling of the extracellular matrix (ECM). Although the role of TGFβ1 in the regulation of ECM protein synthesis is well established, its involvement in the regulation of enzymes, such as MMPs, is still not well understood. In this study, we investigated the relationship between TGFβ1 and MMP-9/MMP-2 in in vitro differentiating myoblasts isolated from rat slow-twitch Soleus or fast-twitch Extensor Digitorum Longus (EDL) muscles. We hypothesized that differences in the regulation of MMPs contribute to the varying repair efficiencies between muscle types.MethodsUsing siRNA to silence TβR1 expression, suramin as a competitive inhibitor of the TβR1 receptor, and inhibitors of both the canonical and non-canonical TGFβ signaling pathways, we characterized the role of TGFβ1 in regulating MMP-9 and MMP-2 during differentiation of myoblasts derived from slow-twitch Soleus and fast-twitch EDL muscles in vitro.Results and discussionOur results demonstrated that blocking TGFβ1 signaling pathway significantly improved regeneration in slow-twitch Soleus muscle, altered the activity of MMP-9 and MMP-2 in in vitro differentiating myoblasts, and Soleus and EDL-derived myoblasts differ in their response to inhibition of TGFβ-dependent signaling pathways.